The Licensing of Parasitic Gaps - García Mayo, María del Pilar (Miscelánea: A Journal of English and American Studies, 1995)
One of the syntactic characteristics attributed to parasitic gaps in the literature is that they require the presence of an S-S variable. This licensing variable must not c-command the parasitic gap. In this paper I argue that an operator/variable pair is not the only essential environment allowing the licensing of parasitic gaps in Spanish at S-S contrary to what happens in English where only variables license these constructions. This paper adopts the theoretical assumptions of Government and Binding theory.